Correlation Between Serum C-Reactive Protein (CRP) and Soluble Cd40 Ligand (sCD40L) with Disease Activity by Modified Rodnan Skin Score (mRSS) in Systemic Sclerosis Patients in Indonesia - Widi Palupi Ayu Padmandani; Sumartini Dewi; Laniyati Hamijoyo (Indonesian Journal of Rheumatology, 2018)
Introduction: Systemic Sclerosis (SSc) is a chronic autoimmune disease which presents immunological, endothelial dysfunction, skin and organs fibrosis. The inflammatory process is an important pathophysiology of systemic sclerosis. Disease activity assessment using clinical parameters of Modified Rodnan Skin Score (mRSS) changes and inflammatory laboratory parameters of C-Reactive Protein (CRP), Erytrocyte Sedimentation Rate (ESR) and soluble CD40 ligand. The European Scleroderma Study Group (EscSG) Activity Index uses CRP. CRP is higher sensitivity and specificity than ESR (80% and 91.2%). The study aims to evaluate the correlation between CRP and sCD40L with disease activity by mRSS.Methods: This research was a cross-sectional study, and data of mRSS and sCD40L were obtained from the study, "Blind Clinical Trials Extract Ciplukan Herbs on Clinical Improvement of Skin Disorders, Inflammatory Process, Immunology and Fibrosis in Scleroderma Patientsâ€. CRP examination was done by using the rest samples of the study, conducted in December 2017. Data analysis with Rank-Spearman and Pearson Correlation..Result: There were fifty-eight subjects with mean age 38 Â± 11 years old. Most of subjects were female (94.8%) and with a late disease duration > 2 years (74.1 %). Subjects consisted of 35 (60.3%) diffuse SSc and 23 (39.7 %) limited SSc. CRP was measured by Turbidimetric Immunoassay. Median (range) CRP serum was 2.89 (0.16â€“17.29) mg/L, while the median of sCD40L was 6457 (1018â€“17976) pg/mL, and the median of mRSS was 17 (4â€“36). There was no correlation between CRP and sCD40L with mRSS (r = -0.134, p = 0.167; and r = 0.023, p = 0.433).Conclusion: There was no correlation between CRP and sCD40L serum with mRSS in systemic sclerosis patients.